2014
DOI: 10.1080/01916122.2014.948221
|View full text |Cite
|
Sign up to set email alerts
|

Substructural components in the sporoderm of the Family Cyatheaceae

Abstract: Taylor & Francis makes every effort to ensure the accuracy of all the information (the "Content") contained in the publications on our platform. However, Taylor & Francis, our agents, and our licensors make no representations or warranties whatsoever as to the accuracy, completeness, or suitability for any purpose of the Content. Any opinions and views expressed in this publication are the opinions and views of the authors, and are not the views of or endorsed by Taylor & Francis. The accuracy of the Content s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
1
2
0
3
Order By: Relevance
“…A crosssection view of threads for this species allow to observe the margins and very electron-dense centers, reminiscent of the ones present in some Dicksonia species (Tryon and Lugardon 1991). The substructure of the threads observed in M. speluncae shows similarities with that mentioned by several authors for lycophytes (Rowley 1995, Wittborn et al 1998, ferns (Marquez and Morbelli 2015) and angiosperms (Rowley 1981, 1987, Blackmore 1990. In all of these cases, the authors described them as formed by helical subunits displayed around an axis or central channel.…”
Section: Discussionsupporting
confidence: 81%
“…A crosssection view of threads for this species allow to observe the margins and very electron-dense centers, reminiscent of the ones present in some Dicksonia species (Tryon and Lugardon 1991). The substructure of the threads observed in M. speluncae shows similarities with that mentioned by several authors for lycophytes (Rowley 1995, Wittborn et al 1998, ferns (Marquez and Morbelli 2015) and angiosperms (Rowley 1981, 1987, Blackmore 1990. In all of these cases, the authors described them as formed by helical subunits displayed around an axis or central channel.…”
Section: Discussionsupporting
confidence: 81%
“…The only spore taxa in this study, Cyathidites minor, showed the strongest correlation between fluorescence red values (r = −0.69, p < 0.004) through geological time. This could be due to the chemical composition of Cyathidites minor, the thickened and complex perispore (Marquez and Morbelli, 2014) or due to how this spore chemistry reacts to degradation over geological time.…”
Section: Fluorescence Variation Between Taxamentioning
confidence: 99%
“…Throughout the last 65 million years, the Antarctic continent has undergone a drastic change from a greenhouse environment in the early Paleogene towards an icehouse world in the late Paleogene and Neogene (e.g. Askin S. L. Strother et al: A new approach to identify reworking in Antarctic pollen records and Raine, 2000;Prebble et al, 2006;Anderson et al, 2011;Pross et al, 2012;Bijl et al, 2013;Passchier et al, 2013). The analysis of fossil pollen and spores is one of the most important tools for reconstructing and quantifying past vegetation and terrestrial climate change.…”
Section: Introductionmentioning
confidence: 99%
“…arachnoideum los cordones no presentan diferenciación de electrondensidad a nivel subestructural. No obstante, presentan una gran similitud con las varillas o cordones enrollados helicoidalmente ("coiled rods" o "coiled threads") observados en esporas de Selaginella (Morbelli 1995(Morbelli , et al 2001 y Alsophila (Marquez et al 2009(Marquez et al , 2014. En este sentido, las microverrugas observadas sobre los cordones de P. arachnoideum subsp.…”
Section: Grupo Morfológico Con Cordonesunclassified
“…Además de las Dennstaedtiaceae, son diversos los grupos de plantas en los cuales se han registrado cordones de apariencia y dimensiones similares, los cuales forman parte de la pared de las esporas. Familias de Licofitas como Lycopodiaceae (Rowley 1995;Wittborn et al 1996; y Sellaginelaceae (Morbelli 1995(Morbelli , et al 2001) y de helechos como Dicksoniaceae, Matoniaceae, Vittariaceae, Lindsaeaceae, Pteridaceae (Tryon & Lugardon, 1991) y Cyatheaceae (Marquez et al 2009(Marquez et al , 2010a(Marquez et al , 2010b(Marquez et al , 2014 tienen representantes en donde la esporodermis está constituida por estos elementos. En el caso particular de Lycopodium (Rowley 1995), Selaginella (Morbelli 1995), Cyathea, Alsophila y Spaeropteris (Marquez et al 2014), los autores acordaron en que los cordones estarían conformados por varias subunidades helicoidalmente dispuestas alrededor de un eje o canal central que coincidiría con el modelo de "tuft" propuesto por Rowley (1981, 1988, & Dahl 1982.…”
Section: Hypolepisunclassified